2002
DOI: 10.1089/107632702753725049
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Implantation of Preadipocyte-Seeded PLGA Scaffolds

Abstract: Studies were performed in a long-term effort to develop clinically translatable, tissue engineered adipose constructs for reconstructive, correctional, and cosmetic indications. Rat preadipocytes were harvested, isolated, expanded ex vivo, and seeded within PLGA scaffolds. Preadipocyte-seeded and acellular (control) scaffolds were implanted for 1-12 months. Explanted scaffolds were stained with osmium tetroxide, processed, and counterstained using H&E. Quantitative histomorphometric analysis was performed on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
114
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(117 citation statements)
references
References 17 publications
2
114
0
1
Order By: Relevance
“…The three-dimensional geometry of the native ECM constrains cells during regeneration and provides space for tissue development [25] and in vitro studies have shown that the scaffold geometry promotes preadipocyte differentiation [31]. The architecture of adipose tissue has been reconstructed using adipose-derived stromal cells seeded onto different scaffold materials [6][7][8]13,14]. Hyaluronic acid-based scaffolds have been used clinically to successfully direct chondrocyte development [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three-dimensional geometry of the native ECM constrains cells during regeneration and provides space for tissue development [25] and in vitro studies have shown that the scaffold geometry promotes preadipocyte differentiation [31]. The architecture of adipose tissue has been reconstructed using adipose-derived stromal cells seeded onto different scaffold materials [6][7][8]13,14]. Hyaluronic acid-based scaffolds have been used clinically to successfully direct chondrocyte development [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Materials that meet fundamental requirements such as controlled degradation, cytotoxicity and immunogenity are needed. Research reports have shown successful and reproducible inoculation and culturing of adipocyteand preadipocyte-precursor cells (preadipocytes and progenitors, respectively) on synthetic [6,7] or natural [8] prefabricated scaffolds [9] with subsequent differentiation in vitro or adipose tissue formation in vivo [10]. The scaffolds within these bio-hybrids provided the seeded cells specific attachment or binding sites, shaped the tissue construct and functioned as geometrical environments in which not only cells received their essential cues for a structural cell organization and cellular behaviour but also cellular function was modulated [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Patrick et al demonstrated that ASCs seeded into a PLGA scaffold and implanted subcutaneously into rats showed maximum adipose tissue formation after 2 months, but noted that between 3 and 12 months, a complete loss of reconstructed adipose tissue and degeneration of the PLGA scaffold occurred [77]. This loss of tissue may arise from the degradation of the scaffolding, especially since signs of PLGA degradation were apparent as early as 1 month post-transplantation.…”
Section: Ascs In Synthetic Scaffolds For Soft Tissue Regenerationmentioning
confidence: 99%
“…Structural biopolymer carriers such as sponges or nonwoven meshes provide a permissive microenvironment in which seeded preadipocytes proliferate and differentiate. In the absence of seeded cells, common scaffold materials alone have not been demonstrated as having appreciable adipogenic activity [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Polylactide glycolic acid (PLGA), polyglycolic acid (PGA), hyaluronan, and collagen-I in the form of nonwoven meshes or sponges have been evaluated as three-dimensional carriers for ex vivo expanded preadipocytes with varying success [13][14][15][16]. The in vivo efficacy of constructs in generating mature adipose tissue has been clearly correlated to the in vitro cell inoculation of the scaffolds and on the structure and type of biopolymer used [17].…”
Section: Introductionmentioning
confidence: 99%